Impact of Experiential Marketing and Consumer Trust on Purchase Decisions: Evidence from a Smartphone Retail Business - Jenni Ria Zai; Dedy Lazuardi; Widalicin Januarty (International Journal of Economics Development Research (IJEDR), 2026)
The increasing use of mobile phones in Indonesia has intensified competition in the smartphone retail industry and influenced consumer purchasing behavior. Metta Cell Denai Medan, a local smartphone retailer, has experienced a decline in sales in recent years, indicating reduced consumer purchase interest. Preliminary observations suggest that this decline is associated with suboptimal experiential marketing practices and low levels of consumer trust, particularly in terms of service quality, transparency, and transaction convenience. This study aims to examine the influence of experiential marketing and consumer trust on purchase decisions. This research adopts a quantitative approach using survey data collected from 110 consumers, with the sample size determined based on indicator-based estimation techniques. Data were analyzed using multiple linear regression to assess both partial and simultaneous effects of the independent variables on purchase decisions. The findings reveal that experiential marketing and consumer trust each have a positive and significant effect on purchase decisions. Furthermore, both variables jointly contribute to shaping consumer purchasing behavior. These results highlight the importance of creating meaningful customer experiences and building trust as strategic priorities for improving purchase decisions in the smartphone retail sector.